ダイ12-14ジタイ ナンキョク ロケット ニヨル カブ デンリソウ ノ カンソク - 宮崎, 茂; ミヤザキ, シゲル; MIYAZAKI, Shigeru (国立極地研究所, 1975)
P(論文) The 12th, 13th and 14th Japanese Antarctic Research Expedition parties (1971-73), carried out firings of twenty-one rockets to observe the polar ionosphere and auroral phenomena at Syowa Station(69°00'S, 39°35'E; geomagnetic lat. 69.6°S, long. 77.1°E), Antarctica. The electron density profiles of the ionosphere in disturbed conditions were obtained. The results of analyses and discussions are given in this report. departmental bulletin paper